THE PERFORMANCE OF GREEN MATERIAL IN WATER FILTRATION TOWARD THE POWER OF HYDROGEN (PH) AND TOTAL DISSOLVED SOLIDS (TDS) - Sirun; Syafril Syafar; Lukman Hakim Nasution; Jeni Lukita Juana Prawita; Galen Aquitha Surya de Gathy (International Journal of Innovations in Engineering Research and Technology, 2021)
The level of water’s power of Hydrogen (pH) and Total Dissolve Solid (TDS) do not meet the standard which is dangerous for human consumption. The result of well water measurements at MTs Negeri 5 Rokan Hulu shows that the pH and TDS levels of water are 5.5 mg/l, and 3.2 mg/l. While the natural material such as coconut shells, bagasse is quite abundant and can be used for the water filtration process. However, in order to find out its capabilities, experimental research was carried out by first making a water filtration device from Poly Vinyl Chloride pipe of 4inch in diameter, 100cm long, 1inch inlet and outlet. The oxidation process was not perfect, the material was pounded using a mortar, washed with clean water, and left to dry in the sun, then it was sieved with a mesh of 5 sieves for Coconut Shell Charcoal (CSC), and a mesh 20 sieves for Bagasse Charcoal (BC). The results of the analysis show that filtration using CSC increased the levels of pH is 4.55(+) mg/l reduced the TDS by 1.42(-) mg/l, and the highest decrease in TDS was 1.63(-) mg/l. Whereas using BC increased the pH level by 1.88(+) mg/l, decreased TDS by 1.74(-) mg/l, and the highest decrease in TDS was 2.30(-) mg/l. But for increasing the pH water level it is best to use the CSC of 5 mesh. On the other hand, for decreasing the TDS of water, it is best to use BC of a mesh 20. It can be concluded that the water filtration process of natural green method is worth to be developed because its pH standard and TDS is within the permissible limits of World Health Organization standards and is very environmentally friendly.